Evaluation of dynamic fracture toughness based reference temperature (T0dy) of modified 9Cr-1Mo steel in phosphorus embrittled and cold-worked condition - Sathyanarayanan S.; Moitra A.; Samuel K.G.; Sasikala G.; Ray S.K.; Singh V. (My University, 2025)
In the present study, the DBTT of a high phosphorus bearing modified 9Cr-1Mo steel in normalized and tempered (N&T) condition and also after 5% and 10% cold work, has been evaluated by extending the reference temperature (T0) based Master Curve approach to dynamic loading conditions. The reference temperature in dynamic loading condition (T0dy) thus determined is found to be significantly high for the N&T Mod.9Cr-1Mo steel as compared to plain 9Cr-1Mo steel. Cold-work effect was not found to be significant in T0dy evaluation of Mod.9Cr-1Mo steel. The high T0dy of the present Mod.9Cr-1Mo steel is attributed to a fracture initiation mechanism predominated by decohesion of prior austenitic grain boundaries at the fatigue pre-crack front. This is attributed to segregation of phosphorus along the prior austenitic grain boundaries causing embrittlement, supported by SEM and Secondary Ion Mass Spectrometry (SIMS) observations. © 2007 Elsevier B.V. All rights reserved.